Stratified Approaches to Antiplatelet Therapies Based on Platelet Reactivity Testing - Ostrowska, Małgorzata; Kubica, Jacek; Adamski, Piotr; Kubica, Aldona; Eyileten, Ceren; Postula, Marek; Toma, Aurel; Hengstenberg, Christian; Siller-Matula, Jolanta M. (Frontiers in Cardiovascular Medicine, 2019)
Antiplatelet therapy with P2Y12 receptor inhibitors (clopidogrel, prasugrel, ticagrelor, cangrelor) is a cornerstone of medical therapy after percutaneous coronary interventions. Significant prevalence of high on-treatment platelet reactivity (HTPR) on clopidogrel treatment led to introduction of more potent P2Y12 inhibitors: prasugrel (a third generation thienopyridine), ticagrelor, and cangrelor (cyclopentyl-triazolo-pyrimidines). Nevertheless, more potent platelet inhibition and resulting low on-treatment platelet reactivity (LTPR) has led to increased risk of major bleeding events. These limitations resulted in a need for an individualized antiplatelet therapy approach. This review discusses the current role and future perspectives of diagnostic tools such as platelet function testing to optimize antiplatelet therapy with a focus on deescalating therapies to reduce bleeding risks.